Procalcitonin, c-reactive protein and neopterin levels in patients with coronary atherosclerosis - Ilhan, F; Akbulut, H; Karaca, I; Godekmerdan, A; Ilkay, E; Bulut, V (Taylor & Francis Ltd, 2005)
Objective-Recent studies demonstrate that the serum inflammatory markers increase in patients with atherosclerosis. We aimed to assess whether a difference exists between patients with acute coronary syndrome and patients with stable angina pectoris in respect to serum neopterin, procalcitonin (PCT) and C-reactive protein (CRP) levels. Methods and results-A total of 52 patientss (42 male, 10 female) who had atherosclerosis confirmed by angiography and were being followed up for an acute coronary syndrome were recruited and for control group, 45 patients with stable angina pectoris (SA) (35 male and 10 female) who underwent coronary angiography, were examined. Serum concentrations of neopterin, CRP and PCT in the study group (acute coronary syndrome) were compared to control group (stable angina pectoris).The mean neopterin level of the study group was 22.47 +/- 2.93 nmol/l, the mean CRP level was 30.40 +/- 8.05 mg/l and the mean PCT level was 0.40 +/- 0.04 ng/ml. In control group these levels were 12.26 +/- 0.61 nmol/l (p < 0.05), 5.26 +/- 0.64 mg/l (p < 0.001) and 0.19 +/- 0.02 ng/ml (p < 0.001), respectively. Conclusion-In the presented study our results showed that these markers can be useful for the assessment of inflammation related to atherosclerosis.
Keywords: neopterin; procalcitonin; C-reactive protein; atherosclerosis